2018
DOI: 10.3382/ps/pey110
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci affecting production and biochemical traits in a unique Japanese quail resource population

Abstract: The objective of the current study was to identify QTL associated with body weight, growth rate, egg quality traits, concentration of selected blood plasma, and yolk lipids as well as concentration of selected macro- and microelements, color, pH, basic chemical composition, and drip loss of breast muscle of Japanese quail (Coturnix japonica). Twenty-two meat-type males (line F33) were crossed with twenty-two laying-type females (line S22) to produce a generation of F1 hybrids. The F2 generation was created by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 59 publications
1
13
0
1
Order By: Relevance
“…The present study found a genome-wide significant QTL for EW at the first stage of egg-laying on chromosome 10 positioned at 21.0 cM. A QTL responsible for EW was reported on chromosome 1 at a position of 4 cM for the Japanese quail [ 31 ]. A previous study identified four QTL for the EW trait on chromosomes 1, 3, 18, and 18 positioned at 193, 156, 61, and 62 cM, respectively [ 51 ].…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…The present study found a genome-wide significant QTL for EW at the first stage of egg-laying on chromosome 10 positioned at 21.0 cM. A QTL responsible for EW was reported on chromosome 1 at a position of 4 cM for the Japanese quail [ 31 ]. A previous study identified four QTL for the EW trait on chromosomes 1, 3, 18, and 18 positioned at 193, 156, 61, and 62 cM, respectively [ 51 ].…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, a high rate of contiguity, assembly statistics, gene content, chromosomal organization, and synteny conservation exists between the two species [ 42 , 80 ]. Knaga et al [ 31 ] reported QTL for the egg number and egg production rate at positions 36 to 42 cM on chromosome 1 using 30 microsatellite markers. Minvielle et al [ 52 ] reported QTL for egg number and age at first egg positioned at 32 and 34 cM, respectively, on chromosome 6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microsatellite markers for Japanese quail were developed comprehensively in previous studies (Kayang et al, 2000(Kayang et al, , 2002(Kayang et al, , 2004(Kayang et al, , 2006Mannen et al, 2005). They have been used to discover gene loci associated with plumage colour, body weight, meat quality and egg production (Minvielle et al, 2005(Minvielle et al, , 2006Miwa et al, 2005;Ori, Esmailizadeh, Charati, Mohammadabadi, & Sohrabi, 2014;Rezvannejad, Yaghoobi, & Rashki, 2014;Tavaniello et al, 2014;Moradian et al, 2016;Knaga et al, 2018); however, the chromosomal position of these markers had remained undetermined. We recently developed more than 100 microsatellite DNA markers from Japanese quail based on the whole-genome sequence, covering chromosomes 1 to 28 and the Z and W sex chromosomes (Kawahara-Miki et al, 2013).…”
Section: Validity Of 20 Microsatellite Markers For Genetic Assessmentmentioning
confidence: 99%